Low Tidal Volume Ventilation in Patients without Acute Respiratory Distress Syndrome: A Paradigm Shift in Mechanical Ventilation - Jed Lipes; Azadeh Bojmehrani; Francois Lellouche (Critical Care Research and Practice)
Protective ventilation with low tidal volume has been shown to reduce morbidity and mortality in patients suffering from acute lung injury (ALI) and acute respiratory distress syndrome (ARDS). Low tidal volume ventilation is associated with particular clinical challenges and is therefore often underutilized as a therapeutic option in clinical practice. Despite some potential difficulties, data have been published examining the application of protective ventilation in patients without lung injury. We will briefly review the physiologic rationale for low tidal volume ventilation and explore the current evidence for protective ventilation in patients without lung injury. In addition, we will explore some of the potential reasons for its underuse and provide strategies to overcome some of the associated clinical challenges.